2012
DOI: 10.1088/0004-637x/750/1/23
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Similar Expansion Model for Use in Solar Wind Transient Propagation Studies

Abstract: Since the advent of wide-angle imaging of the inner heliosphere, a plethora of techniques have been developed to investigate the three-dimensional structure and kinematics of solar wind transients, such as coronal mass ejections, from their signatures in single-and multi-spacecraft imaging observations. These techniques, which range from the highly complex and computationally intensive to methods based on simple curve fitting, all have their inherent advantages and limitations. In the analysis of single-spacec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
212
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(216 citation statements)
references
References 25 publications
4
212
0
Order By: Relevance
“…Davies et al (2012) found that the two models described so far can be considered as two extremes of a common geometry. They use a more generalised HMF-like analysis, in which the circular CME front is not fixed to the Sun, which they call a self-similar expansion (SSE).…”
Section: Harmonic Mean Fitting (Hmf)mentioning
confidence: 97%
See 2 more Smart Citations
“…Davies et al (2012) found that the two models described so far can be considered as two extremes of a common geometry. They use a more generalised HMF-like analysis, in which the circular CME front is not fixed to the Sun, which they call a self-similar expansion (SSE).…”
Section: Harmonic Mean Fitting (Hmf)mentioning
confidence: 97%
“…This diagram follows the notation used by Davies et al (2012) and Möstl et al (2011) and uses d 0 instead of r sc .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Even for an observer at a fixed longitude, a different part of the CME will contribute to the imaged radiance at any given time (Xiong et al 2013). Various techniques have been developed that enable the spatial locations and propagation directions of CMEs to be inferred, based on fitting their moving radiance patterns (e.g., Sheeley et al 2008;Rouillard et al 2008;Thernisien et al 2009;Liu et al 2010;Lugaz et al 2010;Möstl et al 2011;Davies et al 2012). However, the determination of interplanetary CME kinematics, and propagation direction in particular, is somewhat ambiguous (Howard & Tappin 2009;Davis et al 2010;Davies et al 2012;Howard & DeForest 2012;Xiong et al 2013;Lugaz & Kintner 2013).…”
Section: Heliospheric White Light Observationsmentioning
confidence: 99%
“…Time-elongation maps (J-maps) are usually constructed by stacking differenced radiance between observed sky maps along a fixed position angle (sometimes background subtracted images are used instead of difference images). Using such J-maps, transients such as CMEs are manifested as inclined streaks (e.g., Sheeley et al 2008;Rouillard et al 2008;Xiong et al 2011;Harrison et al 2012;Davies et al 2012;Xiong et al 2013). As a propagating transient is viewed at larger elongations, its WL signatures become fainter.…”
Section: Thomson Scattering Wl Formulaementioning
confidence: 99%